Polimorfismo de α e β - esterases em variedades de Stevia Rebaudiana Bert. Bertoni - Marochio, Carlos Alexandre (2010)
The (Stevia rebaudiana Bertoni) is a dicot shrub belonging to the family Compositae, which occurs spontaneously in the region of Serra do Amambaí between Brazil and Paraguay. This species has on its leaves sweeteners sweets especially the stevioside and rebaudioside-A, whose sweetness is 300 times that of sucrose, and the product is highlighted by the lack of calories and is much used in special diets. The seedling production of stevia is via seed or cuttings and the selection of plant material to be used for the training of most productive fields, is performed based on morphological and anatomical characters, however the genetic variation of plants analyzed at the molecular level has been still a relatively unexplored subject. The identification of loci and / or alleles linked to important agronomic features, it seems to be a prospect of new opportunities to support the processes of selection. The purpose of this study is to establish appropriate conditions for the analysis of isozymes α and β-esterases in stevia leaves to estimate the diversity among different plants populations and landraces cultivated in the region of Maringá-PR/Brazil. The material used came from four populations grown in different regions near, and the cultivation of these plants of stevia are usually carried out by small landowners and the area devoted to cultivation is around 1 ha. To extract the esterase isozymes leaves were at an early stage of development. We collected about 30 samples of the population P1, 100 population samples P2, P3, 204 population 94 population samples P4, were analyzed in polyacrylamide gel. After developing the areas of activity for the isozymes α and β-esterases were estimated allele frequencies and parameters of genetic diversity, proportion of polymorphic loci, the average number of alleles per locus and polymorphic loci, observed heterozygosity and expected. The analysis of esterase isozymes with the substrates α-naphthyl acetate and β-naphthyl acetate in leaf samples of four populations of Stevia rebaudiana studied showed the occurrence of several esterase isozymes, encoded by at least eight loci. Polymorphism analysis of α and β-esterases in stevia leaves showed that the selection pressure adopted in populations grown for commercial purposes has reduced genetic diversity in the species, considering the high level of observed heterozygosity in these populations.